Thematic Review of Sukuk Ijarah Issued in Nigeria: An Opportunity for Economic Development - Kareem, Ibraheem Alani Abdul; Mahmud, Mohd. Sadad bin; Ganiyy, Abdul Fattah Abdul (Jurnal Iqtisaduna, 2020)
Ijarah Sukuk is becoming one of the most improved products in Islamic finance. It has become an alternative source of financing and liquidity for both private and public sectors. Also, it plays important role in development of the economy of Muslim and no-Muslim countries. The objective of this paper is to clarify the concept of Sukuk Ijarah and discuss its opportunity for economic development of the country. Also, the issues and challenges related to the implementation of Islamic finance particularly Sukuk by the Federal government of Nigeria (FGN) and also as an alternative to conventional bond. The paper adopts content analysis of relevant previous studies. Findings reveal the potential of Sukuk ijarah as an alternative for rapid economic growth and its functional role in attracting government and client to invest in it. Furthermore, the authors observe that misunderstanding among religious leaders is a major challenge to the growth of Islamic banks and implementation of Sukuk in Nigeria. It is recommended that workshops, seminars and conferences are to be organized by Islamic centres, financial institutions and academicians in Universities to spread knowledge and create awareness among Nigerians Muslims and non-Muslims about benefit and advantage of Islamic finance products and Sukuk in particular.